2015
DOI: 10.1371/journal.pone.0131190
|View full text |Cite
|
Sign up to set email alerts
|

Investigating impact of Vascular Endothelial Growth Factor Polymorphisms in Epithelial Ovarian Cancers: A Study in the Indian Population

Abstract: Epithelial ovarian cancer is one of the increasingly incident malignancies that is notorious because of its evasiveness for early diagnosis and high mortality rates. Epithelial ovarian cancers are highly dependent on pathologic vasculature and Vascular Endothelial Growth Factor is known to be one of the most efficient angiogenic factors. Polymorphisms of the VEGF gene, in this study, were assessed for association with the malignancy and other clinico-pathological factors. 300 case samples and 320 age and mensu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…Many environmental and lifestyle factors are involved in the development of ovarian cancer, including early menarche, late menopause, the choice not to or inability to bear children, higher body mass index, family history of cancer, and long-term use of estrogen-replacement therapy and ovulation-inducing drugs (Brekelmans, 2003;Romero and Bast, 2015). Previous studies have reported that hereditary factors also contribute to ovarian cancer development, such as BRCA2, PALB2, X-ray repair cross-complementing group 2, MTHFR, calcium-sensing receptor, and vascular endothelial growth factor genes (Janardhan et al, 2015;Nakagomi et al, 2015;Shi and Shen, 2015;Su et al, 2015;Yan et al, 2015;Zhai et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Many environmental and lifestyle factors are involved in the development of ovarian cancer, including early menarche, late menopause, the choice not to or inability to bear children, higher body mass index, family history of cancer, and long-term use of estrogen-replacement therapy and ovulation-inducing drugs (Brekelmans, 2003;Romero and Bast, 2015). Previous studies have reported that hereditary factors also contribute to ovarian cancer development, such as BRCA2, PALB2, X-ray repair cross-complementing group 2, MTHFR, calcium-sensing receptor, and vascular endothelial growth factor genes (Janardhan et al, 2015;Nakagomi et al, 2015;Shi and Shen, 2015;Su et al, 2015;Yan et al, 2015;Zhai et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…We found that the T allele in the asthma group was present in a significantly higher proportion than in the control group. The VEGF rs3025039 SNP is not only associated with asthma (Lachheb et al, 2008); like the VEGF rs3025020 polymorphism, rs3025039 is also associated with other diseases, for example, bisphosphonate-related osteonecrosis of the jaw (Choi et al, 2015) and ovarian cancers (Janardhan et al, 2015). Compared with healthy controls, the frequency of the T allele of rs3025039 is significantly higher in patients with HCH (He et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial growth factor polymorphisms have been implicated in the susceptibility to several cancers including breast, cervical, ovarian, colorectal and lung cancers. There are only two studies in literature investigating the −2578, +405, +936, and −141 locuses of VEGF gene .…”
Section: Discussionmentioning
confidence: 99%